2010
DOI: 10.1103/physreve.82.066303
|View full text |Cite
|
Sign up to set email alerts
|

Strong polymer-turbulence interactions in viscoelastic turbulent channel flow

Abstract: This paper is focused on the fundamental mechanism(s) of viscoelastic turbulence that leads to polymer-induced turbulent drag reduction phenomenon. A great challenge in this problem is the computation of viscoelastic turbulent flows, since the understanding of polymer physics is restricted to mechanical models. An effective state-of-the-art numerical method to solve the governing equation for polymers modeled as nonlinear springs, without using any artificial assumptions as usual, was implemented here on a thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 62 publications
(123 reference statements)
12
70
0
Order By: Relevance
“…In other words, the turbulence is mainly sustained by the polymers, as already recognised in previous studies [7,18,20]. On the other hand, the polymer production for the two other components of the diagonal is negative (see Figures 5(c)), indicating a transfer of energy from the flow to the polymers.…”
Section: Reynolds Stress Transportsupporting
confidence: 68%
See 1 more Smart Citation
“…In other words, the turbulence is mainly sustained by the polymers, as already recognised in previous studies [7,18,20]. On the other hand, the polymer production for the two other components of the diagonal is negative (see Figures 5(c)), indicating a transfer of energy from the flow to the polymers.…”
Section: Reynolds Stress Transportsupporting
confidence: 68%
“…The second term, P p ij , is the polymer stress work. In particular, P p ii represents the transfer of energy between the mean turbulent kinetic energy and the mean elastic energy of the polymers [7,20]. This term can be either positive or negative, and a positive value corresponds to an energy transfer from the polymers to the turbulence.…”
Section: Reynolds Stress Transportmentioning
confidence: 99%
“…Fujimura et al (2016) verified the bead-spring chain model through comparison with experiments and the finite elastic nonlinear extensibility-Peterlin (FENE-P) model, in which polymer dynamics is represented in the Eulerian frame of reference (Bird et al, 1987), and investigated the influence of the spring constant on the drag reduction effect. Their statistics are in good qualitative agreement with experimental results and with numerical results obtained using the FENE-P model (Dallas et al, 2010). Additionally, they analyzed the budget of Reynolds stress, and reported that the results for energy transport between turbulent flow and polymer models support the trends observed in the study with the FENE-P model by Dimitropoulos et al (2001).…”
Section: Influence Of Length Of Polymer Aggregation On Turbulent Fricsupporting
confidence: 77%
“…Time advancement uses the typical fractional step method utilized in most DNSs of turbulence. The rheological parameters adopted here are consistent with those used in previous simulations of polymer drag reduction (11,12,(44)(45)(46). We use a maximum polymer extension of L = 200, β = 0:9, and Wi* = 8.…”
Section: Methodsmentioning
confidence: 97%